2021
DOI: 10.9734/jpri/2021/v33i40a32232
|View full text |Cite
|
Sign up to set email alerts
|

Design and Identification of Lead Compounds Targeting Nipah G Attachment Glycoprotein by In Silico Approaches

Abstract: Nipah virus (NiV) caused several outbreaks in Asian countries, including the latest one from the Kerala state of India. There is no drug available against NiV till now, despite its urgent requirement. There are reports about the anti-influenza viral drug Favipiravir, which has positively affected the Nipah virus in vitro models. In the current work, we have provided a computational screening for NiV inhibitors. Twenty-two designed compounds from favipiravir and Nipah glycoprotein, 3D11, were chosen and perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…26,27 With significant updates to functional modules, predictive models, explanations, and the user interface, ADMETlab 2.0 has a greater capacity to assist medicinal chemists in accelerating the drug research and development pro-cess. [28][29][30] The SMILES string of each compound was pasted separately and submitted. The evaluation results were then downloaded as a PDF file, and the scores were tabulated.…”
Section: Toxicity Predictionmentioning
confidence: 99%
“…26,27 With significant updates to functional modules, predictive models, explanations, and the user interface, ADMETlab 2.0 has a greater capacity to assist medicinal chemists in accelerating the drug research and development pro-cess. [28][29][30] The SMILES string of each compound was pasted separately and submitted. The evaluation results were then downloaded as a PDF file, and the scores were tabulated.…”
Section: Toxicity Predictionmentioning
confidence: 99%
“…Computational study related to favipiravir and its derivatives were also performed to check their effectiveness towards NiV-G protein [66]. Favipiravir shows a relatively good performance in the experimental work too [57].…”
Section: Nipah G (Niv-g) Protein Target and Computational Drugmentioning
confidence: 99%
“…The study indicated that piperazine-substituted favipiravir derivatives have a higher ability to bind than the original favipiravir structure. James et al studied 22 favipiravir derivatives by incorporating heterocyclic groups (moieties such as pyrazole, imidazole, and pyrazino) in favipiravir [66]. All derivatives were subjected to molecular docking for the Nipah G-protein (PDB ID:3D11) target followed by physical property evaluations and ADMET studies.…”
Section: Nipah G (Niv-g) Protein Target and Computational Drugmentioning
confidence: 99%